Development of Video Learning Media based on Filmora in Technology Topics for Elementary Students - Patras, Yuyun Elizabeth; Naibaho, Matthew M; Karmila, Nita; Marini, Arita; Hidayat, Rais (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
In this study, researchers aim to develop an innovation in video learning media based on Filmora in technology topics for elementary students. This product is developed using the Research and Development (RnD) method, and using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Research begins by finding out what needs the school needs, especially grade 3 by analyzing the curriculum, students, then making product designs, developing the product, then validating the product with experts in their fields, finally conducting limited trials with 29 elemenatry students as respondents. The finished product validated by experts’ states that the feasibility level of the product is very feasible with an average value of 91.67%. When conducting a limited trial with 29 students, video learning media fell into the very good category because it scored with an average of 86.72%. Based on the results of the study, it can be concluded that filmora-based video learning media is suitable for use in elementary school.